Strategy PD. Market Jaya in Strengthening Food Security at DKI Jakarta Province - Arief Nasrudin; Rizari Rizari; Ahmad Averus Toana (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The issues raised in this study are related to the strategy of the Pasar Jaya Regional Company in strengthening food security in DKI Jakarta Province. So far, it seems that the fulfillment of food needs has not been effective in increasing the production capacity and distribution of food which is increasingly limited. This causes food instability between regional needs and fulfillment. The reality faced is that the supply of food production continues to increase from year to year, in line with the increasing population growth in the capital city of the State of Indonesia. The research method used is descriptive method with a qualitative approach. The use of this method is intended to systematically realize the facts, and the characteristics of objects and subjects from empirical observations that are carried out correctly by taking into account the various problems related to the strategy of the Pasar Jaya Regional Company in strengthening food security in DKI Jakarta Province. The results of the study indicate that the strategy of the Pasar Jaya Regional Company in strengthening food security in DKI Jakarta Province which continues to grow and develop was stated by Jones (1994: 296) that the Pasar Jaya Regional Company has not been effective in strengthening food security with its pillar activities which include; organization, interpretation, and application to provide benefits for regional economic development by increasing the distribution of food and regional original income for the general public.